Autonomic Imbalance Increases the Risk for Non-alcoholic Fatty Liver Disease - Jung, Inha; Lee, Da Young; Lee, Mi Yeon; Kwon, Hyemi; Rhee, Eun-Jung; Park, Cheol-Young; Oh, Ki-Won; Lee, Won-Young; Park, Sung-Woo; Park, Se Eun (Frontiers in Endocrinology, 2021)
Background: Although autonomic imbalance is associated with an increased risk for metabolic disease, its effects on nonalcoholic fatty liver disease (NAFLD) remains unclear. We aimed to evaluate whether autonomic dysfunction predicts the risk for nonalcoholic fatty liver disease (NAFLD). Methods: A total of 33,899 participants without NAFLD who underwent health screening programs between 2011 and 2018 were enrolled. NAFLD was identified by ultrasonography. Autonomic activity was estimated using heart rate variability (HRV). Time domain [standard deviation of the normal-to-normal interval (SDNN) and root mean square difference (RMSSD)]; frequency domain [total power (TP), low frequency (LF), and high frequency (HF), and LF/ HF ratio were analyzed. Findings: A total 6,466 participants developed NAFLD within a median of 5.7 years. Subjects with incident NAFLD showed decreased overall autonomic modulation and vagal activity with lowered SDNN, RMSSD, HF, normalized HF, compared to those without NAFLD. As the SDNN, RMSSD, TP, LF, and HF tertiles increased, the risk of NAFLD decreased with tertile 1 being the reference group [the hazard ratios (95% confidence intervals) of tertile 3 were 0.90 (0.85–0.96), 0.83 (0.78–0.88), 0.91 (0.86-0.97), 0.93 (0.87-0.99) and 0.89 (0.83-0.94), respectively] after adjusting for potential confounders. The risk for NAFLD was significantly higher in subjects in whom sustained elevated heart rate, normalized LF, and LF/ HF ratio values than in those with sustained decrease in these parameters during follow-up. Conclusions: Overall autonomic imbalance, decreased parasympathetic activity, and recently increased sympathetic activity might increase the risk of NAFLD.